Wiedza i poglądy nauczycieli religii na tematy związane z ochroną i kształtowaniem środowiska naturalnego - Jacek W. Czartoszewski (Studia Ecologiae et Bioethicae)
The article contains an analysis of the investigation about the knowledge and ideas of religion teachers as regards the protection and the shaping of the natural environment and presents the primary problems of the questionnaire, this was carried out in the Diocese of Lomza with a group of 260 people.